Strategy of Village Owned Enterprises in Realizing Independent Villages - Arum Puspita Sari; Isnaini Rodiyah (Universitas Muhammadiyah Sidoarjo, 2022)
The purpose of this study is to analyze and describe the strategy of BUMDes in realizing an independent village in Ketapanrame Village. This research method uses descriptive qualitative research, data collection is done by observation, interviews, documentation and literature study. The technique of determining the informants used purposive sampling technique. In this study, the informants were the Commissioner of BUMDes Ketapanrame, Directors of BUMDes Ketapanrame, the head of the tourism unit, and the community involved in the BUMDes business. The data analysis technique uses the Ari Miles and Huberman analysis model which consists of data collection, data reduction, data presentation and conclusions or verification. The results of this study indicate that the first of the organizational strategy of BUMDes Taman Ghanjaran is carried out in accordance with the vision and mission that has been established so that BUMDes not only pursue profit targets but also become social actors. The two strategies of the Taman Ghanjaran BUMDes program apply 3 strategies, namely meeting market demand, budgeting and planning, of the three strategies supported by marketing that applies free admission to the Taman Ghanjaran area. The three resource support strategies are carried out by developing the capacity of managers and administrators through training and comparative studies conducted at BUMDes which were advanced and successful in order to gain knowledge transfer to be developed in Ghanjaran Park. And fourth, there is an institutional strategy that is supported by partnerships with outside parties to get investors and serve as a promotional place to attract tourists to Ghanjaran Park.